2014
DOI: 10.1088/0169-5983/46/4/041401
|View full text |Cite
|
Sign up to set email alerts
|

Rossby wave instability in astrophysical discs

Abstract: Abstract.A brief review is given of the Rossby wave instability (RWI) in astrophysical discs. In non-self-gravitating discs, around for example a newly forming stars, the instability can be triggered by an axisymmetric bump at some radius r 0 in the disc surface mass-density. It gives rise to exponentially growing non-axisymmetric perturbation [∝ exp(imφ), m = 1, 2..] in the vicinity of r 0 consisting of anticyclonic vortices. These vortices are regions of high pressure and consequently act to trap dust partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 73 publications
(127 reference statements)
0
39
0
Order By: Relevance
“…Many questions remain. For example, how do the Rossby waves affect the protoplanetary disc (Lovelace & Romanova 2014) and how do they affect the evolution of DA white dwarfs and neutron stars (Saio 1982;Berthomieu & Provost 1983;Andersson 1998;Brown & Ushomirsky 2000)?…”
Section: Introductionmentioning
confidence: 99%
“…Many questions remain. For example, how do the Rossby waves affect the protoplanetary disc (Lovelace & Romanova 2014) and how do they affect the evolution of DA white dwarfs and neutron stars (Saio 1982;Berthomieu & Provost 1983;Andersson 1998;Brown & Ushomirsky 2000)?…”
Section: Introductionmentioning
confidence: 99%
“…NL Rossby wave interaction is an important mechanism in the evolution of central scenarios in atmospheric, oceanic and astrophysical fluid dynamics e.g., [13][14][15][16][17], yet, to the best of our knowledge, no explicit mechanistic CRW analysis exists to describe NL wave-wave interactions. In order to study the basic nature of the phenomenon, we choose a simple setup of a shear layer (Fig.…”
mentioning
confidence: 99%
“…Here we will review the salient points that makes the RWI a good candidate to explain the HFQPOs observed in microquasars. See Lovelace & Romanova (2014) for a full review of the RWI in its different domain of application.…”
Section: The Rossby Wave Instability As a Model For Hfqposmentioning
confidence: 99%